DOES FINTECH LENDING DRIVE MSME GROWTH? EVIDENCE FROM BANKING MEDIATION - Jesslyn Anggara; Rafida Khairani; Nasib (ZILLZELL MEDIA PRIMA, 2026)
This study aims to examine the effect of fintech lending on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a particular focus on the mediating role of the banking industry. MSMEs play a crucial role in the Indonesian economy by contributing significantly to gross domestic product and employment; however, limited access to formal financing remains a major constraint to their development. In this context, fintech lending has emerged as an alternative financing mechanism that offers faster, more flexible, and more accessible funding compared to traditional banking services. This study employs a quantitative approach using secondary data obtained from the Financial Services Authority (OJK), the Central Statistics Agency (BPS), and Data Indonesia, covering the period from January 2022 to December 2025, with a total of 48 observations. The data were analyzed using regression analysis and mediation testing with SPSS. The results indicate that fintech lending has a positive and significant effect on MSME growth. In addition, fintech lending also significantly influences the banking industry. Furthermore, the banking industry has a significant positive effect on MSME growth and fully mediates the relationship between fintech lending and MSME growth. These findings suggest that fintech lending and banking institutions operate in a complementary manner, where banking plays a crucial intermediary role in channeling the impact of fintech into MSME development. Overall, this study provides important insights for policymakers, financial institutions, and fintech developers in strengthening an inclusive and sustainable digital financial ecosystem to support MSME growth in Indonesia.